Plans to improve (Journal of Parents and Teachers, 2023)
The word "improvement" surrounds our society and education is affected with it. We are constantly trying to improve ourselves, so it is necessary to know exactly what we want to change and look for ways to achieve it. For this reason, two models for improvement are presented.
Keywords: improve; education; models